Salicornia strobilacea (Synonym of Halocnemum strobilaceum) Grown under Different Tidal Regimes Selects Rhizosphere Bacteria Capable of Promoting Plant Growth - Marasco, Ramona; Mapelli, Francesca; Rolli, Eleonora; Mosqueira, Maria J.; Fusi, Marco; Bariselli, Paola; Reddy, Muppala; Cherif, Ameur; Tsiamis, George; Borin, Sara; Daffonchio, Daniele (Frontiers in Microbiology, 2016)
Halophytes classified under the common name of salicornia colonize salty and coastal environments across tidal inundation gradients. To unravel the role of tide-related regimes on the structure and functionality of root associated bacteria, the rhizospheric soil of Salicornia strobilacea (synonym of Halocnemum strobilaceum) plants was studied in a tidal zone of the coastline of Southern Tunisia. Although total counts of cultivable bacteria did not change in the rhizosphere of plants grown along a tidal gradient, significant differences were observed in the diversity of both the cultivable and uncultivable bacterial communities. This observation indicates that the tidal regime is contributing to the bacterial species selection in the rhizosphere. Despite the observed diversity in the bacterial community structure, the PGP potential of cultivable rhizospheric bacteria, assessed through in vitro and in vivo tests, was equally distributed along the tidal gradient. Root colonization tests with selected strains proved that halophyte rhizospheric bacteria (i) stably colonize S. strobilacea rhizoplane and the plant shoot suggesting that they move from the root to the shoot and (ii) are capable of improving plant growth. The versatility in the root colonization, the overall PGP traits and the in vivo plant growth promotion under saline condition suggest that such beneficial activities likely take place naturally under a range of tidal regimes.